Gorge waterway at Victoria Arm, Vancouver Island, between 1893 and 1900 - Macmunn, Charles (1893)
Caption on image: The Gorge, Victoria Arm PH Coll 1496.7b The Gorge is a long fingerlike inlet of tidal water north of the town of Esquimalt on Vancouver Island. The Gorge waterway was used as a traditional food gathering place by the First Nations people.